EVALUASI KAPASITAS TAMPUNG SUNGAI DI DAERAH ALIRAN SUNGAI DALAM UPAYA PENGENDALIAN DAYA RUSAK - Riman, - (Universitas Widyagama Malang, 2012)
Capacities of streams in the chacthment area have been many who are notable to accommodate the flow of water, causing flooding. This study is to evaluate the capacity of the river basin Kalidawir, using Hec-Ras program. Calculation results with the results obtained by the program, that:1) the design flow when 10-return period (Q10), the value obtained debit existing conditions (run off Q) = 777.590 m3/sec, while the Q10 condition after normalization and retarding basin debit values ​​obtained (Q run off) = 541.250 m3/sec, so that from the retarding basin normalization and manufacturing can reduce discharge (Q) of 236.340 m3/sec, 2) the design flow when the 25-return period (Q25,) values ​​obtained debit existing condition (Q run off) = 919.266 m3/sec, while the Q25 condition after normalization and retarding basin values​​ obtained debit (Q run off) = 650.726 m3/sec, so that from the retarding basin normalization and manufacturing can reduce discharge(Q) of 268.540 m3/secand 3) alternative solutions to control the destructive force of the (dredging sediment) and retarding basin (catchment while during the floods).